Metal bipolar plate three-layer coating applied to fuel cell and preparation method of metal bipolar plate three-layer coating

The three-layer coating for metal bipolar plates in fuel cells, featuring a transition layer of (Ti0.67Cr0.33)1-xNx and a conductive Ru0.99C0.01 outer layer, addresses the issues of corrosion and conductivity, enhancing durability and performance by reducing contact resistance and corrosion current density.

CN119121129AActive Publication Date: 2024-12-13SHENZHEN HYDROGEN ZHIYUAN TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411289699.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

Existing bipolar plate coatings for metal fuel cells face challenges in maintaining high corrosion resistance and conductivity while ensuring long-term durability, with existing materials either being costly, difficult to apply, or leading to increased contact resistance and reduced service life.

Method used

A three-layer coating comprising an inner layer of (Ti0.67Cr0.33)1-xNx and an outer layer of Ru0.99C0.01, with the inner layer acting as a transition layer to improve bonding strength and reduce thermal expansion mismatch, and the outer layer enhancing corrosion resistance and conductivity, prepared using magnetron sputtering and arc ion plating techniques.

Benefits of technology

The three-layer coating significantly reduces corrosion current density by 28%, increases self-corrosion potential by 0.08V, and decreases contact resistance by 50%, thereby extending the service life and improving the performance of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121129A_ABST
    Figure CN119121129A_ABST
Patent Text Reader

Abstract

The invention discloses a metal bipolar plate three-layer coating applied to a fuel cell and a preparation method of the metal bipolar plate three-layer coating, and particularly relates to the technical field of fuel cells. The three-layer coating is (Ti < 0.67 > Cr < 0.33 >) < 1-x > Nx / Ru0. 99C < 0.01 >, and the three-layer coating comprises a coating inner layer (Ti < 0.67 > Cr < 0.33 >) < 1-x > Nx and a coating outer layer Ru0. 99C < 0.01 >. The obtained coating has the advantages of being uniform, compact and high in adhesive force, and the corrosion resistance and the conductivity of a stainless steel matrix can be effectively improved; the (Ti < 0.67 > Cr < 0.33 >) < 1-x > Nx transition layer designed by combining the characteristics of a matrix and an inner and outer coating system can reduce the thermal expansion mismatching degree between the matrix and the coating, meanwhile, the element compatibility of all the layers is improved, and the binding force of the coating is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a three-layer coating for a metal bipolar plate used in a fuel cell and a preparation method thereof, and more particularly to a coating for a stainless steel metal bipolar plate of a proton exchange membrane fuel cell and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cells (PEMFC) are considered to be the ideal clean power generation method at present due to their compact structure, small size, high energy density, high efficiency, rapid start-up, low temperature operation and zero emissions. In PEMFC, the bipolar plate, as one of the core components, is responsible for connecting individual cells in series, parallel or mixed into a battery stack, supporting the structure of the entire battery stack, isolating the reaction gases at the cathode and anode, and discharging the heat and water generated by the battery stack, which is crucial to the performance of the battery stack. At present, bipolar plates are mainly divided into three types: graphite bipolar plates, metal bipolar plates and composite bipolar plates. Metal bipolar plates have the advantages of high strength and easy processing, and the ultra-thin design facilitates large-scale production, thereby improving the specific power of fuel cells. However, there are many corrosive ions in the working environment, such as SO4 2- and F - These ions easily corrode the metal bipolar plate material, forming a passivation layer, which increases the contact resistance between the bipolar plate and the diffusion layer, significantly affecting the output power and durability of the fuel cell stack. Therefore, in order to achieve its commercial application, it is necessary to reduce the surface contact resistance of the metal bipolar plate through surface coating modification and improve its conductivity and corrosion resistance.

[0003] Existing bipolar plate coatings mainly include carbon-based coatings, precious metal coatings, conductive polymer coatings, hydrophobic coatings, and transition metal ceramic compounds. Carbon-based coatings have excellent corrosion resistance, electrical conductivity, and thermal conductivity, and are low in cost, but the deposition efficiency is not high, which limits their large-scale application. Precious metal coatings provide excellent corrosion resistance and conductivity, but are expensive. Conductive polymer coatings such as polyaniline (PANI) and polypyrrole (PPy) provide good protection for bipolar plates, with excellent corrosion resistance and conductivity, but their bonding with the substrate is weak. Hydrophobic coatings reduce the corrosion rate by increasing hydrophobicity, but it is difficult to maintain long-term stability. Transition metal ceramic compounds have excellent physical, chemical, and mechanical properties, can provide good corrosion resistance and stability in the working environment of bipolar plates, while maintaining high conductivity, and are ideal coating materials. However, large particles in the coating may lead to accelerated local corrosion, and columnar crystals may penetrate into the liquid, thus affecting long-term service life.

[0004] Chinese patent CN115663224A, metal composite coating of bipolar plate of proton exchange membrane fuel cell and its preparation method, from the surface of metal plate substrate, it includes composite metal layer and nano-conductive layer covering the surface of composite metal layer in sequence from inside to outside, the thickness of composite metal layer is 5-3000nm, from inside to outside, it includes metal corrosion-resistant layer, metal self-healing layer and metal catalytic layer in sequence; the thickness of nano-conductive layer is 5-500nm, selected from one or more of carbon-based materials graphite, amorphous carbon, graphene, carbon fiber and carbide. After plasma cleaning of metal substrate, firstly deposit metal corrosion-resistant layer on the surface of metal substrate, then alternately deposit metal self-healing layer and metal catalytic layer on the surface of metal corrosion-resistant layer, and deposit nano-conductive layer on the surface of composite metal layer. However, this patent still contains carbon-based material layer, which affects deposition efficiency.

[0005] Chinese patent CN110797545A mainly adopts the following technical solutions: the metal bipolar plate includes a metal substrate and a carbon-based coating; wherein the carbon-based coating is deposited on the metal substrate, and the carbon-based coating includes at least two layers of carbon films deposited in sequence; wherein each layer of carbon film is any one of laser pulse deposited carbon film, magnetron sputtering deposited carbon film, multi-arc ion plating deposited carbon film, and chemical vapor deposited carbon film; the carbon-based coating includes at least two carbon films of laser pulse deposited carbon film, magnetron sputtering deposited carbon film, multi-arc ion plating deposited carbon film, and chemical vapor deposited carbon film. However, in the double-layer structure, the high corrosion current density and high contact resistance will reduce its service life.

[0006] How to select materials to achieve rapid preparation and easy-to-control processes while maintaining high corrosion resistance and conductivity to extend the service life of fuel cells still requires further research. Summary of the invention

[0007] To this end, the present invention provides a three-layer coating of a metal bipolar plate applied to a fuel cell and a preparation method thereof to solve the above-mentioned problems.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] According to a first aspect of the present invention, a three-layer coating for a metal bipolar plate used in a fuel cell is provided, wherein the three-layer coating is (Ti 0.67 Cr 0.33 ) 1-x N x / Ru 0.99 C 0.01 The three-layer coating includes an inner layer (Ti 0.67 Cr 0.33 ) 1-x N x And the outer layer of coating Ru 0.99 C 0.01 .

[0010] The inner layer Ti of the coating of the present invention 0.67 Cr 0.33 、(Ti 0.67 Cr 0.33 ) 1-x N x As a transition layer, it is used to reduce the thermal expansion mismatch between layers, improve the element compatibility of each layer, and increase the bonding strength of the coating; the outer layer of the coating Ru 0.99 C 0.01 The composition coating is used to improve the corrosion resistance and electrical conductivity of the substrate.

[0011] Furthermore, the inner layer of the coating (Ti 0.67 Cr 0.33 ) 1-x N x Contains the first inner layer Ti 0.67 Cr 0.33 With the second inner layer (Ti 0.67 Cr 0.33 ) 1-x N x , wherein the N element is doped in the gas phase.

[0012] Furthermore, the ratio of Ti element to doped Cr element is (1.5-2.5):1.

[0013] Ti of the present invention 0.67 Cr 0.33 It is a modified material of binary layered ceramic titanium-chromium, and the element Cr is doped in proportion at the Ti position. As an example, the ratio of the Ti element to the doped Cr element is preferably about 2:1. After doping, the corrosion resistance and electrical conductivity of titanium-chromium are significantly improved. 0.67 Cr 0.33 The thickness of the coating is about 100nm, the corrosion current density decreases by 40%, the self-corrosion potential increases by about 0.1V, and the contact resistance decreases by about 30%.

[0014] Furthermore, the N element doping ratio is 40 to 55 at.%.

[0015] Furthermore, the first inner layer Ti 0.67 Cr 0.33 The thickness is 50-500nm, the second inner layer (Ti 0.67 Cr 0.33 ) 1-x N x The thickness is 50 to 500 nm, and the thickness of the outer layer of Ru and C composite coating is 2 to 100 nm.

[0016] According to a second aspect of the present invention, a method for preparing a three-layer coating of a metal bipolar plate for a fuel cell is provided, comprising:

[0017] Step 1: Coating inner layer (Ti 0.67 Cr 0.33 ) 1-x N x Preparation

[0018] Ti powder and Cr powder are prepared by sintering in a hot pressing furnace using a hot pressing / solid-liquid phase reaction method; wherein flowing argon is used as a protective gas to prepare Ti 0.67 Cr 0.33 , prepared with flowing nitrogen as protective gas (Ti 0.67 Cr 0.33 ) 1-x N x ;

[0019] Step 2: Coating the outer layer of Ru 0.99 C 0.01 Preparation

[0020] A mixture of ruthenium and carbon is used to apply arc discharge to the ruthenium target to generate high-temperature plasma, evaporate ruthenium and introduce carbon-containing gas as a carbon source. Carbon elements are introduced into the coating through plasma reaction. By adjusting the evaporation rates of ruthenium and carbon, the Ru / C ratio of the coating is controlled to be 0.99 / 0.01, and the outer layer of the coating Ru 0.99 C 0.01 .

[0021] Furthermore, the inner coating (Ti 0.67 Cr 0.33 ) 1-x N x The Ru and C combination coatings were deposited on the metal bipolar plates using a magnetron sputtering device; the Ru and C combination coatings were deposited using an arc ion plating device.

[0022] As an example, the coating target material of the inner coating is (Ti 0.67 Cr 0.33 ) 1-x N x The powder materials for preparing the target material include Ti powder and Cr powder, which are sintered in a hot pressing furnace by hot pressing / solid-liquid phase reaction method. The sintering temperature is 1000℃~1600℃, the temperature is kept for 20~100min, the hot pressing pressure is 15~75MPa, and flowing argon and nitrogen are used as protective gases respectively to obtain Ti 0.67 Cr 0.33 Target and (Ti 0.67 Cr 0.33 ) 1-x N xTarget material. The target material of the outer coating is a mixture of ruthenium and carbon. Arc discharge is applied to the ruthenium target to generate high-temperature plasma, evaporate ruthenium and introduce carbon-containing gas (such as ethylene, methane, etc.) as a carbon source. Carbon elements are introduced into the coating through plasma reaction. The evaporation rates of ruthenium and carbon are adjusted to control the Ru / C ratio of the coating to 0.99 / 0.01.

[0023] Furthermore, the method of depositing the magnetron sputtering device on the metal bipolar plate includes: adjusting the chamber temperature, keeping warm, turning on the target material DC power supply, controlling the sputtering power and sputtering time for deposition, cooling to room temperature after the deposition, stopping vacuuming and depressurizing. In the present invention, two sputtering power supplies are arranged in a chamber, and when depositing the coating, the sample is suspended on the sample holder of the device, and the column for hanging the sample rotates, and the rotating column revolves with the rotating table to obtain a uniform coating.

[0024] As an example, the method of magnetron sputtering deposition on a metal bipolar plate is as follows: first adjust the chamber temperature to 200-500°C, keep it warm for 10-40 minutes, and then turn on the Ti 0.67 Cr 0.33 The target material is supplied with a DC power supply, the sputtering power is 0.1-2kW, and the sputtering time is 15-45 minutes. After the deposition is completed, the temperature is cooled to room temperature at a rate of 10°C / min under the original vacuum condition, and then the vacuum and pressure are stopped to finally obtain Ti 0.67 Cr 0.33 After changing the target material, the same process was used to prepare (Ti 0.67 Cr 0.33 ) 1-x N x coating.

[0025] Furthermore, the method for deposition by the arc ion plating device includes: first removing pollutants and oxide layers on the surface of the substrate, controlling the working gas pressure in the vacuum chamber by adjusting the pumping speed of the molecular pump, heating the chamber, turning on the DC power supply of the target material, and controlling the arc current, bias voltage and sputtering time. In the present invention, an arc ion plating device with a high-efficiency deposition rate is used to deposit on a metal bipolar plate to improve the bonding strength of the outer coating and increase the compatibility of the coating with the substrate.

[0026] As an example, the deposition method of the arc ion plating equipment is as follows: before the coating is prepared, the vacuum chamber is pre-evacuated to 4×10 -3 After 300 Pa, a 500V negative pulse bias is applied to the substrate to perform backsplash cleaning for 3 to 15 minutes to remove pollutants and oxide layers on the substrate surface. Then, the Ar flow valve is opened, and the gas flow rate is 50mL / min. The working gas pressure in the vacuum chamber is controlled by adjusting the pumping speed of the molecular pump to maintain it at 0.4Pa. The chamber heating temperature is 100 to 200℃, and the Ru is turned on. 0.99C 0.01 The target material DC power supply has an arc current of 40 to 80 A, a bias voltage of -200 to -400 V, and a sputtering time of 1 to 15 min.

[0027] Furthermore, the method further includes pre-treatment: firstly grinding and polishing the metal bipolar plate, then ultrasonically cleaning the ground metal bipolar plate with acetone, alcohol and deionized water respectively, and finally drying it in nitrogen for standby use. As an example, the cleaning time is 10 to 20 minutes.

[0028] According to a third aspect of the present invention, a three-layer coating for a metal bipolar plate for a fuel cell is provided for use in a metal bipolar plate for a proton exchange membrane fuel cell.

[0029] The present invention has the following advantages:

[0030] The present invention firstly adopts magnetron sputtering technology to form two layers of transition metal ceramic compound layers on the inner layer, and then uses arc ion plating technology to deposit Ru on the outer layer. 0.99 C 0.01 The composite coating is used to modulate the gradient structure of the three-layer coating. The coating of the present invention is uniform, dense and has strong adhesion, and can effectively improve the corrosion resistance and electrical conductivity of the stainless steel substrate; the overall coating is prepared quickly and the process is easy to control, thereby significantly improving the performance of the bipolar plate and thus extending the service life of the fuel cell.

[0031] The present invention deposits (Ti) on the metal bipolar plate by two sputtering methods respectively. 0.67 Cr 0.33 ) 1-x N x / Ru 0.99 C 0.01 The three-layer coating has the advantages of uniformity, compactness and high adhesion. The present invention combines the characteristics of the substrate and the inner and outer coating system to design the (Ti 0.67 Cr 0.33 ) 1-x N x The transition layer can reduce the thermal expansion mismatch between the substrate and the coating, while improving the compatibility of the elements of each layer and increasing the bonding strength of the coating; Ru 0.99 C 0.01 The coating is a combination of Ru and C, which can significantly improve the corrosion resistance and conductivity of the coating. 0.67 Cr 0.33 / Ru 0.99 C 0.01 Double-layer coating, the present invention (Ti 0.67 Cr 0.33 ) 1-x N x / Ru 0.99 C0.01 The three-layer coating structure can reduce the corrosion current density by 28%, increase the self-corrosion potential by 0.08V, and reduce the contact resistance by 50%, which can greatly improve the performance of the bipolar plate and thus increase the service life of the fuel cell.

[0032] The preparation method of the coating of the present invention is easy to control and efficient. The middle transition layer is prepared by high-efficiency arc ion plating technology, and the outer coating is prepared by magnetron sputtering technology that can obtain a dense, flat and uniformly structured coating, which is easy to promote industrially. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0034] The structures, proportions, sizes, etc. illustrated in this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with the technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantial technical significance. Any structural modification, change in proportion or adjustment of size shall still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.

[0035] Figure 1 A schematic diagram of the structure of a three-layer coating provided in Example 1 of the present invention; wherein 1-metal substrate; 2-Ti 0.67 Cr 0.33 ; 3-(Ti 0.67 Cr 0.33 ) 1-x N x ; 4-Ru 0.99 C 0.01 ;

[0036] Figure 2 This is a scanning electron microscope cross-sectional view of the coating prepared in Example 1 of the present invention;

[0037] Figure 3 This is a scanning electron microscope surface image of the coating prepared in Example 1 of the present invention;

[0038] Figure 4 This is an electrochemical test-potential scanning diagram of the coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The metal substrate used in the following examples is a metal bipolar plate. 0.67 Cr 0.33 Target and (Ti 0.67 Cr 0.33 ) 1-x N x The target material is prepared by sintering in a hot pressing furnace using a hot pressing / solid-liquid phase reaction method. The sintering temperature is 1000°C to 1600°C, and the temperature is kept for 20 to 100 minutes. The hot pressing pressure is 15 to 75 MPa. Flowing argon and nitrogen are used as protective gases. The original powder materials in the preparation include Ti powder and Cr powder. The ratio used is determined by the Ti content. 0.67 Cr 0.33 The raw material powder is prepared according to the ratio of Ti:Cr in a ratio of 2:1, and wet mixed on a ball mill for 24 to 50 hours, then taken out and naturally air dried, and then sieved for use. The target material obtained in argon is Ti 0.67 Cr 0.33 , the target material obtained in nitrogen is (Ti 0.67 Cr 0.33 ) 1-x N x .

[0041] Example 1

[0042] This embodiment provides a coating suitable for metal bipolar plates of proton exchange membrane fuel cells (structure diagram as shown in FIG. Figure 1 The preparation method of

[0043] Step 1: Prepare the stainless steel metal bipolar plates, and polish the metal bipolar plates step by step with 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# metallographic sandpapers. Then, ultrasonically clean the polished metal bipolar plates with acetone, alcohol, and deionized water for 20 minutes respectively, and then blow dry them in the air for later use.

[0044] Step 2: Deposit Ti by magnetron sputtering 0.67 Cr 0.33 and (Ti 0.67 Cr 0.33 ) 1-x Nx Inner coating:

[0045] First, adjust the chamber temperature to 300°C, keep it warm for 20 minutes, and then turn on the Ti 0.67 Cr 0.33 The target material DC power supply, sputtering power is 1kw, and the sputtering time is 30min. After the deposition is completed, the temperature is cooled to room temperature at a rate of 10℃ / min under the original vacuum condition, and then the vacuum and pressure are stopped to obtain Ti 0.67 Cr 0.33 .

[0046] After switching the target material, the same process was repeated to obtain (Ti 0.67 Cr 0.33 ) 1-x N x (x=0.4~0.55) coating.

[0047] Step 3: Deposit Ru by arc ion plating 0.99 C 0.01 Before coating preparation, the vacuum chamber was pre-evacuated to a back-end vacuum of 4 × 10 -3 Pa, a 500V negative pulse bias is applied to the substrate to perform backsplash cleaning for 10 minutes to remove pollutants and oxide layers on the substrate surface. Then the Ar flow valve is opened, the Ar gas flow rate is 50mL / min, and the working gas pressure in the vacuum chamber is controlled by adjusting the pumping speed of the molecular pump to maintain it at about 0.4Pa, and the chamber heating temperature is 100℃. Turn on the TiC target DC power supply, the arc current is 50A, the bias voltage is -200V, and the sputtering time is 2min.

[0048] After the experiment, the surface and cross-sectional micromorphology of the deposited coating were observed using a scanning electron microscope, and it was found that the three-layer coating was smooth, dense, and well bonded to the substrate. Figure 2 and Figure 3 In the fuel cell simulation environment, Figure 4 As shown, the corrosion current density is 0.65μA / cm2 in a solution of 0.5mol / L H2SO4 and 2ppm HF at 80℃. 2 , the assembly force is 150N / cm 2 Under these conditions, the contact resistance is about 2mΩ·cm 2 .

[0049] Example 2

[0050] This embodiment provides a method for preparing a coating suitable for a metal bipolar plate of a proton exchange membrane fuel cell:

[0051] Step 1: Prepare the stainless steel metal bipolar plates, and polish the metal bipolar plates step by step with 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# metallographic sandpapers. Then, ultrasonically clean the polished metal bipolar plates with acetone, alcohol, and deionized water for 20 minutes respectively, and then blow dry them in the air for later use.

[0052] Step 2: Deposit Ti by magnetron sputtering 0.67 Cr 0.33 and (Ti 0.67 Cr 0.33 ) 1-x N x Inner coating:

[0053] First, adjust the chamber temperature to 500°C, keep it warm for 15 minutes, and then turn on the Ti 0.67 Cr 0.33 The target material was DC powered, the sputtering power was 0.1 kW, and the sputtering time was 45 min. After the deposition was completed, the temperature was cooled to room temperature at a rate of 10 °C / min under the original vacuum conditions, and then the vacuum and pressure were stopped. After switching the target material, the same process was repeated to finally obtain (Ti 0.67 Cr 0.33 ) 1-x N x (x=0.4~0.55) coating.

[0054] Step 3: Deposit Ru by arc ion plating 0.99 C 0.01 Before coating preparation, the vacuum chamber was pre-evacuated to a back-end vacuum of 4 × 10 -3 Pa, a 500V negative pulse bias is applied to the substrate to perform backsplash cleaning for 10 minutes to remove pollutants and oxide layers on the substrate surface. Then the Ar flow valve is opened, the Ar gas flow rate is 50mL / min, and the working gas pressure in the vacuum chamber is controlled by adjusting the pumping speed of the molecular pump to maintain it at about 0.4Pa, and the chamber heating temperature is 200℃. Turn on the TiC target DC power supply, the arc current is 80A, the bias voltage is -200V, and the sputtering time is 15min.

[0055] Example 3

[0056] This embodiment provides a method for preparing a coating suitable for a metal bipolar plate of a proton exchange membrane fuel cell:

[0057] Step 1: Prepare the stainless steel metal bipolar plates, and polish the metal bipolar plates step by step with 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# metallographic sandpapers. Then, ultrasonically clean the polished metal bipolar plates with acetone, alcohol, and deionized water for 20 minutes respectively, and then blow dry them in the air for later use.

[0058] Step 2: Deposit Ti by magnetron sputtering 0.67 Cr 0.33 and (Ti 0.67 Cr 0.33 ) 1-x N x Inner coating:

[0059] First, adjust the chamber temperature to 200°C, keep it warm for 30 minutes, and then turn on the Ti 0.67 Cr 0.33 The target material was DC powered, the sputtering power was 0.1 kW, and the sputtering time was 45 min. After the deposition was completed, the temperature was cooled to room temperature at a rate of 10 °C / min under the original vacuum conditions, and then the vacuum and pressure were stopped. After switching the target material, the same process was repeated to finally obtain (Ti 0.67 Cr 0.33 ) 1-x N x (x=0.4~0.55) coating.

[0060] Then, Ru was deposited by arc ion plating. 0.99 C 0.01 Before coating preparation, the vacuum chamber was pre-evacuated to a back-end vacuum of 4 × 10 -3 Pa, a 500V negative pulse bias is applied to the substrate to perform backsplash cleaning for 10 minutes to remove pollutants and oxide layers on the substrate surface. Then the Ar flow valve is opened, the Ar gas flow rate is 50mL / min, and the working gas pressure in the vacuum chamber is controlled by adjusting the pumping speed of the molecular pump to maintain it at about 0.4Pa, and the chamber heating temperature is 150℃. Turn on the TiC target DC power supply, the arc current is 40A, the bias voltage is -200V, and the sputtering time is 10min.

[0061] Comparative Example 1

[0062] This comparative example provides a method for preparing a coating suitable for a metal bipolar plate of a proton exchange membrane fuel cell:

[0063] In step 2 of this comparative example, only Ti 0.67 Cr 0.33 No longer proceeding (Ti 0.67 Cr 0.33 ) 1-x N xPreparation, other than that in Example 1, Ti 0.67 Cr 0.33 / Ru 0.99 C 0.01 Double coating.

[0064] After the experiment, the surface and cross-sectional microstructure of the deposited coating were observed with a scanning electron microscope, and it was found that the three-layer coating was flat, dense, and well bonded to the substrate. In a fuel cell simulation environment, that is, in a H2SO4 concentration of 0.5 mol / L and 2 ppm HF solution at a temperature of 80°C, a dynamic potential test was conducted, and the corrosion current density was 0.95 μA / cm 2 , the assembly force is 150N / cm 2 Under these conditions, the contact resistance is about 4mΩ·cm 2 .

[0065] Compared to Ti 0.67 Cr 0.33 / Ru 0.99 C 0.01 Double-layer coating, the present invention (Ti 0.67 Cr 0.33 ) 1-x N x / Ru 0.99 C 0.01 The three-layer coating structure can reduce the corrosion current density by 28%, increase the self-corrosion potential by 0.08V, and reduce the contact resistance by 50%, which can greatly improve the performance of the bipolar plate and thus increase the service life of the fuel cell.

[0066] Comparative Example 2

[0067] This comparative example provides a method for preparing a metal composite coating for a proton exchange membrane fuel cell bipolar plate:

[0068] (1) Under vacuum conditions, the metal substrate on the sample holder is cleaned by radio frequency plasma to remove impurities and oxides on the surface of the metal substrate;

[0069] (2) depositing a metal corrosion-resistant layer on the surface of the cleaned metal substrate by magnetron sputtering, wherein the sputtering target material is titanium and the thickness of the metal corrosion-resistant layer is 100 nm;

[0070] (3) depositing a metal self-healing layer on the metal corrosion-resistant layer by a magnetron sputtering method, wherein the sputtering target material is metallic silver and the thickness of the metal self-healing layer is 50 nm;

[0071] (4) depositing a metal catalyst layer on the surface of the metal self-healing layer by a reactive magnetron sputtering method, wherein the sputtering target is metal lanthanum, the reaction gas is oxygen, the thickness of the metal catalyst layer is 50 nm, and the atomic ratio of metal lanthanum in lanthanum oxide is 20%;

[0072] (5) A nano-conductive layer of amorphous carbon is deposited on the surface of the metal catalyst layer by a magnetron sputtering method. The sputtering target is a graphite target, and the thickness of the nano-conductive layer is 100 nm.

[0073] In a fuel cell simulation environment, i.e., H2SO4 concentration of 0.5 mol / L and 2 ppm HF solution, the dynamic potential test was carried out at a temperature of 80°C, and the corrosion current density was 1.2 μA / cm 2 , the assembly force is 150Ncm -2 Under these conditions, the contact resistance is about 4.3mΩ·cm 2 .

[0074] It can be seen that by using the coating of the present invention for the stainless steel metal bipolar plate of the proton exchange membrane fuel cell, the corrosion current density and the contact resistance are significantly reduced, which can greatly improve the performance of the bipolar plate and thus increase the service life of the fuel cell.

[0075] Comparative Example 3

[0076] This comparative example provides a method for preparing a coating suitable for a metal bipolar plate of a proton exchange membrane fuel cell:

[0077] The Ru and C layers used in step 3 are changed to Pt and C layers, and the rest are exactly the same as in Example 1.

[0078] In a fuel cell simulation environment, i.e., H2SO4 concentration of 0.5 mol / L and 2 ppm HF solution, the dynamic potential test was carried out at a temperature of 80°C, and the corrosion current density was 1.2 μA / cm 2 , the assembly force is 150N / cm 2 Under these conditions, the contact resistance is about 3mΩ·cm 2 .

[0079] Comparative Example 4

[0080] This comparative example provides a method for preparing a coating suitable for a metal bipolar plate of a proton exchange membrane fuel cell:

[0081] The Ru and C layers used in step 3 are changed to Ag and C layers, and the rest are exactly the same as in embodiment 1.

[0082] In a fuel cell simulation environment, i.e., a H2SO4 concentration of 0.5 mol / L and a 2 ppm HF solution, the dynamic potential test was carried out at a temperature of 80°C, and the corrosion current density was 1.9 μA / cm 2 , the assembly force is 150N / cm 2 Under these conditions, the contact resistance is about 3.7 mΩ·cm 2 .

[0083] It can be seen that changing the element composition of the outer layer of the coating will significantly increase the corrosion current density and contact resistance, so Ru and C are the best materials for the outer layer of the coating.

[0084] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A three-layer coating for metal bipolar plates used in fuel cells, It is characterized in that The three-layer coating is (Ti 0.67 Cr 0.33 ) 1-x N x / Ru 0.99 C 0.01 The three-layer coating includes an inner layer (Ti 0.67 Cr 0.33 ) 1-x N x And the outer layer of coating Ru 0.99 C 0.01 .

2. A three-layer coating for a metal bipolar plate used in a fuel cell according to claim 1, It is characterized in that The inner layer of the coating (Ti 0.67 Cr 0.33 ) 1-x N x Contains the first inner layer Ti 0.67 Cr 0.33 With the second inner layer (Ti 0.67 Cr 0.33 ) 1-x N x , 1≥x>0, where the N element is doped in the gas phase.

3. A three-layer coating for a metal bipolar plate used in a fuel cell according to claim 2, It is characterized in that The N element doping ratio is 40 to 55 at.%.

4. A three-layer coating for a metal bipolar plate used in a fuel cell according to claim 2, It is characterized in that The first inner layer Ti 0.67 Cr 0.33 The thickness is 50-500nm, the second inner layer (Ti 0.67 Cr 0.33 ) 1-x N x The thickness is 50 to 500 nm, and the thickness of the outer layer of Ru and C composite coating is 2 to 100 nm.

5. The three-layer coating of a metal bipolar plate for a fuel cell according to claim 2, It is characterized in that The ratio of Ti element to doped Cr element is (1.5-2.5):

1.

6. A method for preparing a three-layer coating of a metal bipolar plate for a fuel cell, It is characterized in that include: Step 1: Coating inner layer (Ti 0.67 Cr 0.33 ) 1-x N x Preparation Ti powder and Cr powder are prepared by sintering in a hot pressing furnace using a hot pressing / solid-liquid phase reaction method; wherein flowing argon is used as a protective gas to prepare Ti 0.67 Cr 0.33 , prepared with flowing nitrogen as protective gas (Ti 0.67 Cr 0.33 ) 1-x N x ; Step 2: Coating outer layer Ru 0.99 C 0.01 Preparation A mixture of ruthenium and carbon is used to apply arc discharge to the ruthenium target to generate high-temperature plasma, evaporate ruthenium and introduce carbon-containing gas as a carbon source. Carbon elements are introduced into the coating through plasma reaction. By adjusting the evaporation rates of ruthenium and carbon, the Ru / C ratio of the coating is controlled to be 0.99 / 0.01, and the outer layer of the coating Ru 0.99 C 0.01 .

7. A method for preparing a three-layer coating of a metal bipolar plate for a fuel cell according to claim 6, It is characterized in that The inner layer of the coating (Ti 0.67 Cr 0.33 ) 1-x N x The Ru and C combination coatings were deposited on the metal bipolar plates using a magnetron sputtering device; the Ru and C combination coatings were deposited using an arc ion plating device.

8. A method for preparing a three-layer coating of a metal bipolar plate for a fuel cell according to claim 7, It is characterized in that The method for depositing on the metal bipolar plate by the magnetron sputtering device includes: adjusting the chamber temperature, keeping the chamber warm, turning on the target material DC power supply, controlling the sputtering power and sputtering time for deposition, and after the deposition is completed, cooling to room temperature, stopping vacuuming and releasing the pressure; the method for depositing by the arc ion plating device includes: first removing pollutants and oxide layers on the surface of the substrate, controlling the working gas pressure in the vacuum chamber by adjusting the pumping speed of the molecular pump, heating the chamber, turning on the target material DC power supply, and controlling the arc current, bias voltage and sputtering time.

9. A method for preparing a three-layer coating of a metal bipolar plate for a fuel cell according to claim 7, It is characterized in that The method also includes pre-treatment: first grinding and polishing the metal bipolar plate, then ultrasonically cleaning the ground metal bipolar plate with acetone, alcohol and deionized water respectively, and finally drying it in nitrogen for standby use.

10. Application of a three-layer coating on a metal bipolar plate for a fuel cell in a proton exchange membrane fuel cell metal bipolar plate.

Citation Information

Patent Citations

  • Conductive and corrosion-resistant coating for metal bipolar plate of fuel cell

    CN109346743A

  • Coating and layer system, and bipolar plate, fuel cell and electrolyser

    CN111032903A

  • Metal bipolar plate coating and preparation method thereof

    CN113584441A

  • Fuel cell metal bipolar plate composite coating and preparation method thereof

    CN115020734A

  • Metal bipolar plate double-layer coating TiC / (Ti, Nb) 3AlC2 for fuel cell and preparation method of metal bipolar plate double-layer coating TiC / (Ti, Nb) 3AlC2

    CN116470084A